The Utilization of Instagram as a Health Education and Branding Media at Aysha Islamic Hospital - Indah Mustika Rahmadini; Dumilah Ayuningtyas (International Journal Labs, 2025)
Social media has become a strategic platform in healthcare communication, including for education and institutional branding. This study aims to explore the use of Instagram by Aysha Islamic Hospital as a medium for health education and strengthening the image of the institution. The approach of this research is qualitative descriptive with a case study method. Data was obtained through observation of @rsislamaysha's official Instagram account, interviews with the digital marketing team, and digital documentation. The results showed that Instagram was actively used to deliver educational content, service promotions, patient testimonials, and hospital social activities. Visual communication strategies, integration of Islamic values, and two-way interaction are the main strengths in building relationships with audiences. However, the main challenge faced is that the quantitative content effectiveness evaluation system is not optimal. Findings support the critical role of social media that social media has an important role in increasing public health literacy and strengthening the branding of health care institutions.